Industrial Composting of Sewage Sludge: Study of the Bacteriome, Sanitation, and Antibiotic-Resistant Strains - López-González, Juan A.; Estrella-González, María J.; Lerma-Moliz, Rosario; Jurado, Macarena M.; Suárez-Estrella, Francisca; López, María J. (Frontiers in Microbiology, 2021)
Wastewater treatment generates a huge amount of sewage sludge, which is a source of environmental pollution. Among the alternatives for the management of this waste, industrial composting stands out as one of the most relevant. The objective of this study was to analyze the bacterial population linked to this process and to determine its effectiveness for the reduction, and even elimination, of microorganisms and pathogens present in these organic wastes. For this purpose, the bacteriome and the fecal bacteria contamination of samples from different sewage sludge industrial composting facilities were evaluated. In addition, fecal bacteria indicators and pathogens, such as Salmonella, were isolated from samples collected at key stages of the process and characterized for antibiotic resistance to macrolides, β-lactams, quinolones and aminoglycosides families. Metagenomics data revealed that the process clearly evolved towards a prevalence of Firmicutes and Actinobacteria phyla, removing the fecal load. Moreover, antibiotic-resistant microorganisms present in the raw materials were reduced, since these were isolated only in the bio-oxidative phase. Therefore, industrial composting of sewage sludge results in a bio-safe final product suitable for use in a variety of applications.